Cytotoxicity against Human Hepatocellular Carcinoma (HepG2) Cells and Anti-Oxidant Activity of Selected Endemic or Medicinal Plants in Sri Lanka - Jeyaraj Thusyanthan; Nimesha Sulochani Wickramaratne; Kanishka Sithira Senathilake; Umapriyatharshini Rajagopalan; Kamani Hemamala Tennekoon; Ira Thabrew; Sameera Ranganath Samarakoon (Hindawi Limited, 2022)
Hepatocellular carcinoma (HCC) is the most fatal cancer globally with limited treatment options. Plants and herbs have been used to treat cancer and other diseases for a long time by traditional practitioners in Sri Lanka. In the present study, leaf and bark extracts of selected plants were investigated for cytotoxic properties on HepG2 cells. Anti-oxidant activity and total phenolic and flavonoid contents were also determined. Plant extracts that exerted cytotoxic effects on the HepG2 cell line with IC50 <100 μg/mL were tested on normal liver epithelial cells (THLE-3). Out of the 56 extracts, 21 exhibited potent cytotoxic effects (IC50 < 100 µg/mL) on HepG2 cells after 48 h exposure, and 12 were less toxic (IC50 > 100 μg/mL) to THLE-3 normal liver cells. Six extracts exhibited potent radical scavenging activity with EC50 < 100 μg/mL against 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay, while 17 extracts showed potent anti-oxidant activity (Trolox equivalents > 100 mg/g) against ferric reducing anti-oxidant power (FRAP) assay. Out of the 56 extracts, 15 had total phenolic content above 100 mg/g of gallic acid equivalents, and 4 had flavonoid content above 100 mg/g of quercetin equivalents. Among the extracts screened, hexane, dichloromethane, ethyl acetate, and methanol extracts of Allophylus cobbe leaves (IC50 - 9.388, 6.8, 19.95, and 11.3 μg/mL, respectively), Madhuca longiflora bark (IC50 - 14.42 μg/mL), methanol extract of Munronia pinnata bark (IC50 - 52.06 μg/mL), and hexane, dichloromethane, ethyl acetate, and methanol extracts of Adenanthera bicolor (IC50 - 45.86, 27.35, 24.56, and 61.83 μg/mL, respectively) exerted potent cytotoxicity against HepG2 with less toxicity (IC50 > 100 μg/mL) to THLE-3 cells after 48 h of incubation. These findings provide a direction to isolate possible anti-cancer compounds for hepatocellular carcinoma.